The Role of Epigenetics in the Endothelial Cell Shear Stress Response and Atherosclerosis - Dunn, Jessilyn (Int J Biochem Cell Biol, 2015)
Currently in the field of vascular biology, the role of epigenetics in endothelial cell biology and vascular disease has attracted more in-depth study. Using both in vitro and in vivo models of blood flow, investigators have recently begun to reveal the underlying epigenetic regulation of endothelial gene expression. Recently, our group, along with two other independent groups, have demonstrated that blood flow controls endothelial gene expression by DNA methyltransferases (DNMT1 and 3A). Disturbed flow (d-flow), characterized by low and oscillating shear stress (OS), is pro-atherogenic and induces expression of DNMT1 both in vivo and in vitro. D-flow regulates genome-wide DNA methylation patterns in a DNMT-dependent manner. The DNMT inhibitor 5-Aza-2’deoxycytidine (5Aza) or DNMT1 siRNA reduces OS-induced endothelial inflammation. Moreover, 5Aza inhibits the development of atherosclerosis in ApoE(-/-) mice. Through a systems biological analysis of genome-wide DNA methylation patterns and gene expression data, we found 11 mechanosensitive genes which were suppressed by d-flow in vivo, experienced hypermethylation in their promoter region in response to d-flow, and were rescued by 5Aza treatment. Interestingly, among these mechanosensitive genes, the two transcription factors HoxA5 and Klf3 contain cAMP-response-elements (CRE), which may indicate that methylation of CRE sites could serve as a mechanosensitive master switch in gene expression. These findings provide new insight into the mechanism by which flow controls epigenetic DNA methylation patterns, which in turn alters endothelial gene expression, regulates vascular biology, and induces atherosclerosis. These novel findings have broad implications for understanding the biochemical mechanisms of atherogenesis and provide a basis for identifying potential therapeutic targets for atherosclerosis.